1975
DOI: 10.1136/gut.16.6.443
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic innervation of the human alimentary tract and its relation to function.

Abstract: SUMMARY The intrinsic innervation of the human gut has been studied in strips of circular and longitudinal muscle removed at operation. Studies using drugs to stimulate the nerves within strips of human gut muscles have indicated marked regional differences in innervation (Bennett and Whitney, 1966a;Bennett, 1968;Bennett, 1970). It is of particular interest that these differences seem to correlate with regional functions and the dependence on extrinsic innervation. The drugs used were ganglion stimulants such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…Similar differences in sensitivity occur with PGF2,, in the normal human ileum and colon in vivo (Cummings, Newman, Misiewicz, MiltonThompson & Billings, 1973;Hunt, Dilawari & Misiewicz, 1975), and with PGE2, PGF2a or PGI2 in rat isolated stomach and colon (Gilmore, Vane & Wyllie, 1968;Omini, Moncada & Vane, 1977). Various other gradients occur in the human gut, such as biochemical and electrical activities (Alvarez, 1948), the muscle response to gastrin (Waller & Misiewicz, 1979) and innervation (Bennett & Stockley, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences in sensitivity occur with PGF2,, in the normal human ileum and colon in vivo (Cummings, Newman, Misiewicz, MiltonThompson & Billings, 1973;Hunt, Dilawari & Misiewicz, 1975), and with PGE2, PGF2a or PGI2 in rat isolated stomach and colon (Gilmore, Vane & Wyllie, 1968;Omini, Moncada & Vane, 1977). Various other gradients occur in the human gut, such as biochemical and electrical activities (Alvarez, 1948), the muscle response to gastrin (Waller & Misiewicz, 1979) and innervation (Bennett & Stockley, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The responses we measure may be caused by the interaction of several substances because the intestine contains fibers that are cholinergic, adrenergic, nonadrenergic inhibitory, and noncholinergic excitatory (17). The potential sites of action of tetrodotoxin are also increased by the presence in the small intestine of 12 endocrine cell types (18), for tetrodotoxin may affect not only nerve fibers but paracrine cells, because depolarizing currents cause action potentials similar to those of sympathetic neurons in a wide variety of cells capable of secreting amines or polypeptides (APUD cells) (14).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins appear to facilitate responses mediated by cholinergic nerves in the longitudinal muscle of guinea-pig isolated ileum (for discussion, see Bennett, Eley & Stockley, 1975b As reported previously, the responses of human ileal strips to electrical stimulation are complex (Bennett & Stockley, 1975 Electrical stimulation (20 s trains; 1 ms pulses; 16 V/cm) produced various combinations of relaxations and initial-and after-contractions. n is the number of strips that produced a particular type of response at each frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This probably explains the reduction of nerve-mediated relaxations (both were restored by 5-HT), the enhanced contractions to ACh (Bennett & Stockley, 1975) Milton-Thompson & Billings (1973) found that intravenous prostaglandin F2a in man inhibited intraluminal pressure changes; perhaps it caused a maintained increase in muscle tone but increased the baseline intraluminal pressure only transiently because the intestine is an open tube. Superimposed pressure waves would therefore be smaller.…”
Section: Longitudinal Musclementioning
confidence: 99%